Patients' Evaluation of Intervention by a Medical Clown Visit or by Viewing a Humorous Film Following In Vitro Fertilization and Embryo Transfer - Shevach Friedler MD; Saralee Glasser MA; Gila Levitan MPH; Dana Hadar MSc; Bat-El Sasi BA, RN; Liat Lerner-Geva MD, PhD (SAGE Publishing, 2017)
This study compared responses to an in-person clown visit and a humorous film following in vitro fertilization and embryo transfer. Intervention was a 10-minute clown visit (n = 101) or 10-minute humorous video clip (n = 99). Demographic and fertility-related data and preintervention anxiety scores were collected. Participants completed an Evaluation of Intervention form postintervention. There were no group differences on demographic or fertility-related data or anxiety scores. Findings indicate while participants viewed the intervention positively, the clown visit offered a higher degree of satisfaction in more patients than did the film. Median evaluation scores were significantly higher for the clown visit, specifically reducing anxiety level and being more distracting. Both groups reported that the exposure made the clinic experience more pleasant and did not bother them, and most would recommend incorporating the intervention in routine treatment. However, free-text comments clearly expressed greater enthusiasm to the in-person clown intervention than to the film.